Physician use of persuasion and colorectal cancer screening. Issue 1 (13th September 2014) - Lafata, Jennifer Elston; Wunderlich, Tracy; Flocke, Susan A.; Oja-Tebbe, Nancy; Dyer, Karen E.; Siminoff, Laura A.
Abstract: The impact of patient–physician communication on subsequent patient behavior has rarely been evaluated in the context of colorectal cancer (CRC) screening discussions. We describe physicians' use of persuasive techniques when recommending CRC screening and evaluate its association with patients' subsequent adherence to screening. Audio recordings of N  = 414 periodic health examinations were joined with screening use data from electronic medical records and pre-/post-visit patient surveys. The association between persuasion and screening was assessed using generalized estimating equations. According to observer ratings, primary care physicians frequently use persuasive techniques (63 %) when recommending CRC screening, most commonly argument or refutation. However, physician persuasion was not associated with subsequent screening adherence. Physician use of persuasion may be a common vehicle for information provision during CRC screening discussions; however, our results do not support the sole reliance on persuasive techniques if the goal is to improve adherence to recommended screening.